Ten Points for High-Quality Statistical Reporting and Data Presentation - Pentti Nieminen (Applied Sciences, 2020)
Background: Data analysis methods have become an essential part of empirical research papers, especially in health sciences and medical research. It has previously been reported that a noteworthy percentage of articles have flaws in their statistical reporting. Reporting problems have been a long-term issue, and despite continued efforts to improve the situation, improvements have been far from satisfactory. One explanation is an inadequate assessment of statistical reporting during peer review. This communication proposes a short instrument to assess the quality of data analysis reporting in manuscripts and published papers. Method: A checklist-type instrument was developed by selecting and refining items from previous reports about the quality of statistical reporting in medical journals and from published guidelines for reporting and data presentation. Items were pretested and modified during pilot studies. A total of 160 original medical research articles that were published in 4 journals were evaluated to test the instrument. Interrater and intrarater agreements were examined by comparing quality scores assigned to 40 articles published in a psychiatric journal. Results: The data analysis reporting test consists of nine questions that assess the quality of health research from a reader’s perspective. The composed scale has a total score ranging from 0 to 10 and discriminated between journals and study designs. A high score suggested that an article had a good presentation of findings in tables and figures and that the description of analysis methods was helpful to readers. Interrater and intrarater agreements were high. Conclusion: An applicable checklist for quickly testing the statistical reporting quality of manuscripts and published research papers was developed. This instrument aims to improve the quality of empirical research in scientific fields where statistical methods play an important role.